KOLABORASI EDU-KREATIF: MEMBENTUK KARAKTER ANAK SEHAT, AKTIF, DAN CERIA MELALUI PEMBIASAAN PHBS SEJAK DINI DI TK KB GRIYA PERMATA - Selli Dosriani Sitopu; Magdalena Ginting; Rosita Saragih; Poniyah Simanullang; Hetti Marlina Pakpahan; Zulkarnain Nasution (Lafadz Jaya Publisher, 2026)
Early childhood health problems in suburban areas like Tanjung Anom, Deli Serdang Regency, bordering Medan, are still dominated by infectious diseases such as diarrhea and URI due to the lack of Clean and Healthy Living Behavior (CHLB/PHBS) habituation. At TK KB Permata Jaya, this issue is compounded by teachers' limitations in designing interactive health education media, resulting in low student PHBS practice. This community service aims to build healthy, active, and cheerful child characters through an